Investir un territoire de frontière : le culte des Matronae dans la Civitas Ubiorum en Germanie Inférieure - Audrey Ferlut (Frontière·s)
Germanic tribes from the other bank of the Rhine River progressively settled where the Eburones, annihilated by Caesar in 53 BCE., lived. Among them, the Ubii. Migrating by waves after 38 BCE. to the frontier of the Roman Empire, they built new political and social structures and new religious practices while they appropriated roman culture and habits. Among the cults in the newly created Civitas Ubiorum, the cult to the Matronae, concentrated in the east of the Civitas, became central and dominant. The militaries and the elites were key agents in the circulation of the Matronae. Other social groups, inserted in the curiae, participated in the municipalisation of the cult while those social groups became civic institutions in the civitas then.Born in rural communities in the 1st century CE. before reaching the Roman colonies at the very end of that century, the cult to Matronae spread on a double scheme: some very local cults to some Matronae in small sanctuaries which sometimes revealed a massive amount of inscriptions and a provincial cult to the Matronae Aufaniae that spreads from Bonn and Köln. Through that process, the Matronae were the most revered deities in Germania Inferior, without any other cult able to equal them.